The Effectiveness of Using Cake Application to Improve Students' Speaking Achievement Across Multiple Intelligences - Ika Permata Permata Sari; Lasim Muzammil; Siti Mafulah (Prodi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Darul Ulum Lamongan*, 2025)
In the modern era of digital learning, enhancing students' English-speaking abilities remains challenging, especially when learners possess diverse cognitive abilities. Mobile-assisted language learning (MALL) applications, such as the Cake application, provide promising solutions by addressing students' diverse intelligences. This research aimed to (1) determine whether there is a significant difference in speaking achievement between students taught using the Cake application and those taught using YouTube, and (2) to determine whether multiple intelligences—specifically linguistic, visual-spatial, and interpersonal intelligences—influence students' speaking performance. A quasi-experimental methodology was used, with two randomly assigned classes: one experimental group using the Cake program and one control group utilizing YouTube. After six sessions, a posttest was administered to measure pupils' speaking abilities. The results showed significant improvements in the experimental group (p = 0.032 < 0.05). A factorial two-way ANOVA revealed a significant interaction between media consumption and multiple intelligences (p = 0.000, < 0.05). These findings suggest that incorporating digital materials linked to students' cognitive profiles can significantly enhance speaking abilities. The research emphasizes the value of individualized, intelligence-based approaches to teaching the English language.